Policy Evaluation of Regulation Number 1429 of 2012 Concerning Arrangement of Study Program in the Islamic Religious College and Its Impact on PAI Study Program in IAIN Central Java (EDUKASIA, 2021)
The purpose of this study was to evaluate the implementation of Islamic Education Regulation Number 1429 of 2012 concerning Study Program Arrangements in Islamic Religious Colleges and their implementation at the Islamic Education Study Program, Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) in Central Java, namely Islamic Education Study Program (PAI) and Education Management Study Program Islam (MPI).  This research is field research which using qualitative data. The results of the study found four main problems, namely: (1) Policy of Faculty of Tarbiyah at IAIN in developing PAI into the PAI Study Program and MPI Study Program; (2) The efforts of Faculty of Tarbiyah IAIN in developing theIslamic Education Study Program became the PAI Study Program and MPI Study Program; (3) Supporting factors and obstacles faced by Faculty of Tarbiyah, IAIN in developing the Islamic Education Study Program into PAI Study Program and MPI Program Study at Faculty of Tarbiyah IAIN; and (4) Impacts faced by the Faculty of Tarbiyah IAIN and Islamic Education Study Program in developing Islamic Education Study Program into the PAI Study Program and the MPI Study Program of the IAIN Faculty of Tarbiyah.